Implementasi Sistem Informasi Analisis Beban Kerja Pada Pegawai di Lingkungan Kecamatan Sawahan Kota Surabaya - Nurmaulidya, Salsabila; Rosyidatuzzahro Anisykurlillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Workload Analysis is an important process that must be carried out in every agency, both private and government, in order to determine the needs for the number and type of Employee and Employee positions with a Work Agreement based on position analysis and workload analysis. The existence of this Workload Analysis information system can make it easier for organizations to make decisions on employee workload analysis in planning employee arrangements to make them more efficient and accurate. This research uses descriptive research with qualitative methodology. By conducting direct observations and interviews, using the Miles and Hubbermen model data analysis method which consists of three stages, the first is data reduction, the second is data display and then the final stage is drawing conclusions. According to George C. Edward III there are several aspects that influence how well policies are implemented, therefore it is important to take a closer look at how ABK information system policies are implemented. These aspects include; bureaucratic structure, resources, disposition, and communication. Based on research findings, these four factors are adequate; the only thing that is limited is the resource element. Not all employees understand how to operate the ABK information system. This is not a serious obstacle for Sawahan District in implementing this policy.